Correlação da coalescência de microcavidades com as propriedades mecânicas e elétricas de fios para Tx e Dx de energia elétrica da liga base Al-0,5%Cu-[0,24-0,28]%Fe modificada com teores de silício - MONTEIRO, Valmor Capanema Oliveira (Universidade Federal do Pará, 2014)
In this study, na attempt is made to establish the influence of the concentration [0.5, 0.7 and 0.9]% Si as modifiers of alloys Al-0,05% Cu-[0.24 to 0.28]%Fe, evaluated by aspects that took into account operational parameters such as horizontal unidirectional leaks: Speeds (Vs) and Exchange Solidification (Tx). After cutting and machining cylindrical profiles were obtained with diameters of 9.5mm and length of 120mm, from which, after the cold working operations, were obtained wires with diameters of 2.7, 3.0, 3.8 and 4.0 mm. These profiles were subjected to electrical characterization on the basis of the electrical conductivity, tomechanical characterization based on assays stress/strain, emphasizing elongation [%], and structural characterization longitudinal sections, with emphasis on distribution of second phase particles, and aspect of the fracture, with emphasis on the relationship L/W length (L) and width (W) of the dimples.